Advances in Groundwater Flow and Solute Transport: Pushing the Hidden Boundary - Wen, Zhang (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
In recent decades, the study of groundwater flow and solute transport has advanced into new territories that are beyond conventional theories, such as Darcy's law and Fick's law. The studied media have changed from permeable porous and fractured ones to much less permeable ones, such as clay and shale. The studied pore sizes have also changed from millimetres to micro-meters or even nano-meters. The objective of this Special Issue is to report recent advances in groundwater flow and solute transport that push the knowledge boundary into new territories which include, but are not limited to, flow and transport in sloping aquifer/hillslopes, coupled unsaturated and saturated flow, coupled aquifer-vertical/horizontal/slant well flow, interaction of aquifer with connected and disconnected rivers, non-Darcian flow, anomalous transport beyond the Fickian scheme, and flow and transport in extremely small pore spaces such as shale and tight sandstones. Contributions focusing on innovative experimental, numerical, and analytical methods for understanding unconventional problems, such as the above-listed ones, are encouraged, and contributions addressing flow and transport at interfaces of different media and crossing multiple temporal and spatial scales are of great value